Cerebral Blood Flow Changes after Brain Injury in Human Amyloid-Beta Knock-in Mice. Issue 6 (June 2013) - Abrahamson, Eric E; Foley, Lesley M; DeKosky, Steven T; Hitchens, T Kevin; Ho, Chien; Kochanek, Patrick M; Ikonomovic, Milos D
Traumatic brain injury (TBI) is an environmental risk factor for Alzheimer's disease (AD). Increased brain concentrations of amyloid-β (Aβ) peptides and impaired cerebral blood flow (CBF) are shared pathologic features of TBI and AD and promising therapeutic targets. We used arterial spin-labeling magnetic resonance imaging to examine if CBF changes after TBI are influenced by human Aβ and amenable to simvastatin therapy. CBF was measured 3 days and 3 weeks after controlled cortical impact (CCI) injury in transgenic human Aβ-expressing APP NLh/NLh mice compared to murine Aβ-expressing C57Bl/6J wild types. Compared to uninjured littermates, CBF was reduced in the cortex of the injured hemisphere in both Aβ transgenics and wild types; deficits were more pronounced in the transgenic group, which exhibited injury-induced increased concentrations of human Aβ. In the hemisphere contralateral to CCI, CBF levels were stable in Aβ transgenic mice but increased in wild-type mice, both relative to uninjured littermates. Post-injury treatment of Aβ transgenic mice with simvastatin lowered brain Aβ concentrations, attenuated deficits in CBF ipsilateral to injury, restored hyperemia contralateral to injury, and reduced brain tissue loss. Future studies examining long-term effects of simvastatin therapy on CBF and chronic neurodegenerative changes after TBI are warranted.